Proceedings of the Eighth International Conference on Information and Communication Technologies and Development 2016
DOI: 10.1145/2909609.2909615
|View full text |Cite
|
Sign up to set email alerts
|

Increased Wage Inequality via ICTs

Abstract: Globalisation and technological advances have affected workers' livelihoods. This study analysed how capital investment in ICTs at the workplace affected marginalised low wage workers in a large sample of firms (n=632) in Singapore. We found that social investment by the state for ICTs investments in workplaces led to a significant negative, albeit marginal, reduction in wage growth. We argue that these findings are supported by economic theory, and propose that government investment balance towards higher-ord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Specifically, Webster (2007) postulated that the advent of Information Communication Technologies (ICTs) was a key contributing factor to workers' job anxieties. In terms of the impact on income inequality, Loh and Chib (2016) found that a higher use of ICTs, in the workplace, did not correspond to higher wages for its employees. In fact, the opposite happened -ICT use at work was associated with declining wages for its workers (Loh & Chib, 2016).…”
Section: Income Inequality From Skill-biased Technological Changementioning
confidence: 95%
See 1 more Smart Citation
“…Specifically, Webster (2007) postulated that the advent of Information Communication Technologies (ICTs) was a key contributing factor to workers' job anxieties. In terms of the impact on income inequality, Loh and Chib (2016) found that a higher use of ICTs, in the workplace, did not correspond to higher wages for its employees. In fact, the opposite happened -ICT use at work was associated with declining wages for its workers (Loh & Chib, 2016).…”
Section: Income Inequality From Skill-biased Technological Changementioning
confidence: 95%
“…In terms of the impact on income inequality, Loh and Chib (2016) found that a higher use of ICTs, in the workplace, did not correspond to higher wages for its employees. In fact, the opposite happened -ICT use at work was associated with declining wages for its workers (Loh & Chib, 2016).…”
Section: Income Inequality From Skill-biased Technological Changementioning
confidence: 95%